Fresh produce value chains in Kenya: Challenges and prospects for enhanced market access and inclusion of smallholders - Amare, Mulubrhan; Shiferaw, Bekele; Adeyanju, Dolapo; Andam, Kwaw S.; Mariara, Jane (International Food Policy Research Institute, 2023)
Contract farming is one potential mechanism that smallholder farmers in developing countries can use to participate in and benefit from domestic and global value chains (Okello and Swinton 2007; Barrett et al. 2012; Minot and Sawyer 2016; Ruben 2017; Ton et al. 2017). Linking smallholder farmers more directly with national and global consumers should increase both the demand and producer prices for their fresh produce. Increased access to and participation in such value chains increases farm income earned by smallholders. Improvements in inclusion and efficiency of value chains are vital to enhance the effectiveness of contracting models, and to enhance the market access and integration of smallholders. Inclusion is important because large buyers, including processors, modern retailers, and exporters, are often hesitant to engage with small and marginal farmers and may prefer working through brokers, which reduces benefits to farmers. Also, market integration is becoming increasingly important for smallholders in order to avoid marginalization of the less organized sector in the more organized, growing global fresh produce market (Ruben 2017; Ton et al. 2017).